Placing fashion: art, space, display and the building of luxury fashion markets through retail design - Crewe, Louise (SAGE, 2015)
This paper explores the performative and affective affordances enshrined in contemporary fashion space. Fashion markets need to be placed in a much more serious conceptual way. Whilst much critical attention has been focused on the geographies of fashion production, it is also important to explore the spaces in which fashion is displayed, consumed, exhibited and performed and thus to understand how fashion markets are ordered, regulated and maintained in space and through time. In order to ‘place’ fashion space within the contemporary city the paper focuses on a set of alliances between art and fashion in the making of current consumption space. It is argued that the collaboration between art and fashion opens up a means to critically explore how representational worlds are brought into being and offers new ways to understand how creative activity can be rooted in (and reflective of) broader social, economic and cultural concerns. Such collisions and collusions represent a key means of making and shaping value and reveal the significance of visuality, singularity and judgement in determining commodity and brand meaning and value